Advances in information and computer security : 13th International Workshop on Security, IWSEC 2018, Sendai, Japan, September 3-5, 2018, Proceedings /: 13th International Workshop on Security, IWSEC 2018, Sendai, Japan, September 3-5, 2018, Proceedings. ([2018]) - Unknown
No abstract available